2011
DOI: 10.1177/0300985811404710
|View full text |Cite
|
Sign up to set email alerts
|

Pathology ofClostridium perfringensType C Enterotoxemia in Horses

Abstract: Clostridium perfringens type C is an important cause of enteritis and enterocolitis in foals and occasionally in adult horses. The disease is a classic enterotoxemia, and the enteric lesions and systemic effects are caused primarily by beta toxin, 1 of 2 major toxins produced by C. perfringens type C. Until now, only sporadic cases of C. perfringens type C equine enterotoxemia have been reported. We present a comprehensive description of the lesions in 8 confirmed cases of type C enterotoxemia in foals and adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
108
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(112 citation statements)
references
References 23 publications
3
108
0
1
Order By: Relevance
“…It has now been clearly established that certain C. perfringens strains are capable of inducing necrotic enteritis in broilers, pigs, lambs, horses, felines, and humans 13, 35, 36, 37, 38. Currently, the cause of C. perfringens overgrowth in the gastrointestinal tracts of humans or other mammals, including dogs, is not always known.…”
Section: Discussionmentioning
confidence: 99%
“…It has now been clearly established that certain C. perfringens strains are capable of inducing necrotic enteritis in broilers, pigs, lambs, horses, felines, and humans 13, 35, 36, 37, 38. Currently, the cause of C. perfringens overgrowth in the gastrointestinal tracts of humans or other mammals, including dogs, is not always known.…”
Section: Discussionmentioning
confidence: 99%
“…On post mortem examination, the small intestine, and eventually also the large intestine, is diffusely hemorrhagic and necrotic, sometimes with the presence of ulcers and pseudomembrane. Mucosal and submucosal thrombosis is also common (HOWARD-MARTIN et al, 1986;DROLET et al, 1990;DIAB et al, 2012).…”
Section: Horsesmentioning
confidence: 99%
“…For older foals or adult horses, the predisposing factors are not completely known; however, malnutrition, trypsin deficiency, pancreatic diseases and a diet rich in trypsin inhibitors may predispose an animal to C. perfringens type C infection (DIAB et al, 2012). Some authors also reported that certain antibiotics could play a role in C. perfringens type C infection, although this is only speculative (DIAB et al, 2012). Co-infection of C. perfringens type C and C. difficile, another common clostridial foal enteropathogen, could also be possible (UZAL et al, 2012).…”
Section: Horsesmentioning
confidence: 99%
See 2 more Smart Citations